PENGARUH OBJEK WISATA TASIKRIA TERHADAP PERUBAHAN SOSIAL MASYARAKAT DI DESA MOKUPA KECAMATAN TOMBARIRI - Romelin M. Waha; Charles R. Ngangi; Ellen G. Tangkere (Sam Ratulangi University, 2016)
The objective of this research is to know the effect of social change especially attitude and social value to the decrease of Tasikria tourism object at Mokupa Village Tombariri Dictrict.The collecting has been conducted for one year, from December, 2014 to December, 2015. The obtained data are primary and decundary data. The primary data are obtained directly from the government at Mokupa Village, Tombariri Sub-Disctrit. The sampling uses purposive sampling chosen at Mokupa Village involving village society such as teacher, government employee, To know the effect of social change especially attitude, it uses Likert Scale Analysis. The research result showed that the effect of social change to tourism object at Mokupa Village Tombariri Sub-Dictrict was high based on attitude and social value of local society.*jnkd*